ICT as a tool for collaboration in the classroom - challenges and lessons learned - Jacob Davidsen; Marianne Georgsen (Stockholm University Press, 2010)
This paper presents data and results from a study on collaboration and self-directed learning in two second year-classes in a Danish school. Learners at ages eight and nine use interactive screens as a learning tool, and more than 150 hours of video data have been collected from the classrooms over a period of ten months. Through detailed inspection of video data, patterns of interaction and ways of collaborating are analysed. Analyses show that the participation patterns of the young learners are crucial to their learning outcome, and also that the role and actions of the teacher are decisive factors in the successful employment of this specific learning design. This paper presents examples of detailed analyses of parts of the data material. Among other things, findings include that collaboration between learners have gender issues, and that addressing topics such as collaborative and communicative skills require careful pre-teaching planning and classroom-observations by the teachers in charge.